Betaine Inhibits Interleukin-1β Production and Release: Potential Mechanisms - Xia, Yaoyao; Chen, Shuai; Zhu, Guoqiang; Huang, Ruilin; Yin, Yulong; Ren, Wenkai (Frontiers in Immunology, 2018)
Betaine is a critical nutrient for mammal health, and has been found to alleviate inflammation by lowering interleukin (IL)-1β secretion; however, the underlying mechanisms by which betaine inhibits IL-1β secretion remain to be uncovered. In this review, we summarize the current understanding about the mechanisms of betaine in IL-1β production and release. For IL-1β production, betaine affects canonical and non-canonical inflammasome-mediated processing of IL-1β through signaling pathways, such as NF-κB, NLRP3 and caspase-8/11. For IL-1β release, betaine inhibits IL-1β release through blocking the exocytosis of IL-1β-containing secretory lysosomes, reducing the shedding of IL-1β-containing plasma membrane microvesicles, suppressing the exocytosis of IL-1β-containing exosomes, and attenuating the passive efflux of IL-1β across hyperpermeable plasma membrane during pyroptotic cell death, which are associated with ERK1/2/PLA2 and caspase-8/A-SMase signaling pathways. Collectively, this review highlights the anti-inflammatory property of betaine by inhibiting the production and release of IL-1β, and indicates the potential application of betaine supplementation as an adjuvant therapy in various inflammatory diseases associating with IL-1β secretion.